APLIKASI SERBUK CANGKANG TELUR DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI SEMANGKA (Citrullus vulgaris Schard) PADA TANAH GAMBUT MEULABOH - Iwandikasyah Putra; Nana Ariska; Yuliatul Muslimah (Universitas Teuku Umar, 2019)
This study aims to determine the effect of eggshell powder application and manure on the growth and production of watermelon on meulaboh peat soils and whether these two factors were real or not. This research was conducted in the experimental garden of the Faculty of Agriculture, Teuku Umar Meulaboh University from December 2018 to April 2019. This study used a 4 x 4 factorial randomized block design with three replications. The egg shell powder (C) factor consisted of four the levels are: C0 = control, C1 = 300 kg / ha (2.25 g / polybag), C2 = 400kg / ha (3 / polybag), C3 = 500 kg / ha (3.75 g / polybag) (Syam et al., 2014). Factor manure (K) consists of four levels, namely: K0 = control, K1 = 50 tons / ha (0.375 kg / polybag), K2 = 100 tons / ha (0.75 kg / polybag), K3 = 150 tons / ha (1,125 kg / polybag) Observation parameters include; plant length (cm), number of leaves, age of flowering, fruit length (cm), diameter of fruit (cm), weight of fruit (kg), production of tons / ha. The results showed that the dose of eggshell had a significant effect on increasing soil pH, a very significant effect on the length of the 15 HST plant but had no significant effect on the length of the 30 HST plant, the number of leaves 15 and 30 HST, and the flowering phase. Significantly affect the fruit length and fruit diameter. However, no significant effect on fruit weight and tons / ha production. Manure has a very significant effect on the length of watermelon plants aged 15 HST. However, the effect was not significant at the age of 30 HST. Significant effect on the number of watermelon leaves aged 15 HST, however, very significant effect on the age of 30 HST. Very significant influence on watermelon flowers and very significant effect on fruit length, diameter, fruit weight, and tons / ha production. There was no interaction between eggshell and manure from all treatments. Keywords: Eggshell Powder, Manure, Watermelon, Peatland